Own-account workers in Europe: Flexible, mobile, and often inadequately insured - Karin Schulze Buschoff; Claudia Schmidt (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
The European Union is currently experiencing a kind of 'renaissance of selfemployment'. As part of this trend, the share of self-employed workers who are operating their enterprises without the support of dependent employees is growing particularly evidently. Members of this category of self-employed are known as 'ownaccount workers'. Proceeding from the theory of transitional labour markets, the authors develop a concept with which mobility rates and mobility patterns can be used to compare the dynamics of own-account work (entries, exits and duration) in five different European countries (Germany, the Netherlands, Italy, United Kingdom and occasionally Sweden). Against this background, the insurance coverage offered to the self-employed as well as that enjoyed by persons entering or exiting the status of selfemployment are then observed and compared across the different countries. – – Die selbstständige Erwerbsarbeit hat in den letzten Jahrzehnten in der Mehrzahl der EUMitgliedsstaaten an Bedeutung gewonnen. Insbesondere der Anteil von Klein- und Solo-Unternehmen weist eine steigende Tendenz auf. Im Kontext der Theorie der Übergangsarbeitsmärkte wird ein Mobilitätskonzept entwickelt und die Dynamik der Solo-Selbstständigkeit anhand von Mobilitätsraten und Mobilitätsmustern (Eintritte, Austritte, Dauer) in fünf europäischen Ländern (Deutschland, den Niederlanden, Italien, Großbritannien und Schweden) verglichen. Abschließend wird auf die national unterschiedliche institutionelle Absicherung von Mobilität bzw. von Übergängen eingegangen. Am Beispiel der staatlichen Rentenversicherungssysteme wird aufgezeigt, ob Statuswechsel in und aus der Solo- Selbstständigkeit heraus in sozialversicherungsrechtlicher Hinsicht in den betrachteten Ländern mit Nachteilen verbunden sind.
Keywords: 330